6+10j-3=-5+9j

Simple and best practice solution for 6+10j-3=-5+9j equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+10j-3=-5+9j equation:



6+10j-3=-5+9j
We move all terms to the left:
6+10j-3-(-5+9j)=0
We add all the numbers together, and all the variables
10j-(9j-5)+6-3=0
We add all the numbers together, and all the variables
10j-(9j-5)+3=0
We get rid of parentheses
10j-9j+5+3=0
We add all the numbers together, and all the variables
j+8=0
We move all terms containing j to the left, all other terms to the right
j=-8

See similar equations:

| -10b+7=-3-8b | | 20k+50=20050 | | -5+10z=7z+1 | | -9u+4=-5u-6-2u | | 56x1.12=62.72 | | 2c-1=-1-9c | | 9m+12=4m-28 | | 2s^2+6s+7=0 | | 5w-36=27 | | -4n+1=-5n | | 4-8b=-10b-10 | | 4x-8+5x-20=180 | | 3x+2−x=11x+9 | | 3x+2−x=11x+9. | | (w+5)*w=36 | | -9d=8−8d | | 7x+34+9x+22=180 | | 7x+34+9x+22=90 | | -7−5p=-4p | | -17-3(x+9)=50 | | W+5=36/w | | 5x-10+4x-8=90 | | 3(x-7)^2=75 | | 10h+6-5h+3=5h+9 | | 6x+1=37,x= | | -6(2+4x)=84- | | 8.25s−2.375=10 | | -5v-4(-8-4v)=98 | | -2(1+6x)=82 | | 10=7+9-3c | | 113=17-8x | | 7+9=3c |

Equations solver categories